2020
DOI: 10.1111/echo.14702
|View full text |Cite
|
Sign up to set email alerts
|

The association between the renal resistive index and the myocardial performance index in the general population

Abstract: Objective The renal resistive index (RRI) is the most described measure of renal hemodynamics. The myocardial performance index (MPI) is widely used to assess overall myocardial performance. In this study, we aimed to investigate the relationship between renal hemodynamics, assessed by the RRI, and cardiac functions, assessed by the MPI in the general population. Methods This single‐center, cross‐sectional study included a total of 302 consecutive patients who presented to our outpatient cardiology clinic betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Tedesco et al (30) showed that high RRI (29). A study conducted by Quisi et al (31) showed a significant association between RRI and MPI in the general population. In a study, the association of renal hemodynamics with RHT was examined.…”
Section: Discussionmentioning
confidence: 98%
“…Tedesco et al (30) showed that high RRI (29). A study conducted by Quisi et al (31) showed a significant association between RRI and MPI in the general population. In a study, the association of renal hemodynamics with RHT was examined.…”
Section: Discussionmentioning
confidence: 98%
“…However, central pulse pressure, diastolic trasmitral E and A Doppler flow velocities and velocity time integral of LV outflow tract have also strong correlation with RRI values [23]. More than that, not only that RRI depends on LVEF and myocardial performance index [95], but also it is an independent prognostic marker for atherosclerotic cardiovascular events in patients with preserved EF [96].…”
Section: Renal Resistive Index and The Cardiovascular Systemmentioning
confidence: 98%
“…However, central pulse pressure, diastolic trasmitral E and A Doppler flow velocities, and the velocity time integral of the LV outflow tract also have strong correlation with RRI values [23]. Moreover, not only does the RRI depend on LVEF and the myocardial performance index [92], but it is also an independent prognostic marker for atherosclerotic cardiovascular events in patients with preserved EF [93].…”
Section: Renal Resistive Index and The Cardiovascular Systemmentioning
confidence: 99%